2012
DOI: 10.1021/mp300418r
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Exposed Tryptophan as Substrate Generators for the Antibody Catalyzed Water Oxidation Pathway

Abstract: The reaction of singlet oxygen with water to form hydrogen peroxide was catalyzed by antibodies and has been termed as the antibody catalyzed water oxidation pathway (ACWOP) (Nieva and Wentworth, Trends Biochem. Sci. 2004, 29, 274-278; Nieva et al. Immunol. Lett. 2006, 103, 33-38). While conserved and buried tryptophans in the antibody are thought to play a major role in this pathway, our studies with a monoclonal antibody, mAb-1 and its mutant W53A, clearly demonstrate the role of surface-exposed tryptophans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 44 publications
1
66
0
Order By: Relevance
“…Nonetheless, it has been shown that a hydroxyl radical generated in close proximity to the site of oxidation may be consumed before it can diffuse, which would render mannitol unable to quench the reaction. 42 Data from the Amplex red assay indicates that very little to no hydrogen peroxide was generated when the peptide was incubated with Cu 2C . The data from the bathocuproine assay showed only approximately 15% reduction of Cu 2C to Cu 1C , adding further support that single electron transfer and further generation of various ROS is not the major pathway in Cu 2C -mediated degradation of the hinge peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it has been shown that a hydroxyl radical generated in close proximity to the site of oxidation may be consumed before it can diffuse, which would render mannitol unable to quench the reaction. 42 Data from the Amplex red assay indicates that very little to no hydrogen peroxide was generated when the peptide was incubated with Cu 2C . The data from the bathocuproine assay showed only approximately 15% reduction of Cu 2C to Cu 1C , adding further support that single electron transfer and further generation of various ROS is not the major pathway in Cu 2C -mediated degradation of the hinge peptide.…”
Section: Discussionmentioning
confidence: 99%
“…However, four amino acids; methionine, cysteine, tryptophan and histidine were found to catalyze ozone formation in the presence of singlet oxygen (Yamashita et al, 2008). The common feature of these amino acids is that they are all photooxidizable (Wentworth et al, 2001) as evidenced through numerous studies both in free form and as components of proteins (Zhu et al, 2004;Pattison et al, 2012;Lundeen and McNeill, 2013;Sreethara et al, 2013;Amano et al, 2014;Liu et al, 2014).…”
Section: Water Oxidation Pathwaymentioning
confidence: 99%
“…Despite only a few amino acids being oxidized in the presence of singlet oxygen, they are able to generate adequate ozone and hydrogen peroxide (Sreethara et al, 2013). Therefore, it is possible to mention that protein molecules lacking these amino acids are not able to generate ozone.…”
Section: Water Oxidation Pathwaymentioning
confidence: 99%
“…Another recent publication focuses on the role of exposed Trps on the surface of antibodies that results in the generation of reactive oxygen species such as singlet oxygen and superoxides upon exposure to light (Sreedhara et al, 2013). In particular, antibodies are capable of catalyzing a water oxidation pathway termed the antibody-catalyzed water oxidation pathway (Wentworth et al, 2001), and surface-exposed Trps in the antibody during exposure to light catalyze this process (Figure 3.8(a)).…”
Section: Trp Oxidation In Mabsmentioning
confidence: 99%
“…Samples: 1 = T0; 2 = 24 h; 3 = 48 h; 4 = 72 h; and 5 = 96 h light exposure under ICH guidelines. Reproduced fromSreedhara et al (2013).…”
mentioning
confidence: 99%